Large‐Grain Tin‐Rich Perovskite Films for Efficient Solar Cells via Metal Alloying Technique. Issue 11 (24th January 2018) - Tavakoli, Mohammad Mahdi; Zakeeruddin, Shaik Mohammed; Grätzel, Michael; Fan, Zhiyong
Abstract: Fast research progress on lead halide perovskite solar cells has been achieved in the past a few years. However, the presence of lead (Pb) in perovskite composition as a toxic element still remains a major issue for large‐scale deployment. In this work, a novel and facile technique is presented to fabricate tin (Sn)‐rich perovskite film using metal precursors and an alloying technique. Herein, the perovskite films are formed as a result of the reaction between Sn/Pb binary alloy metal precursors and methylammonium iodide (MAI) vapor in a chemical vapor deposition process carried out at 185 °C. It is found that in this approach the Pb/Sn precursors are first converted to (Pb/Sn)I2 and further reaction with MAI vapor leads to the formation of perovskite films. By using Pb–Sn eutectic alloy, perovskite films with large grain sizes up to 5 µm can be grown directly from liquid phase metal. Consequently, using an alloying technique and this unique growth mechanism, a less‐toxic and efficient perovskite solar cell with a power conversion efficiency (PCE) of 14.04% is demonstrated, while pure Sn and Pb perovskite solar cells prepared in this manner yield PCEs of 4.62% and 14.21%, respectively. It is found that this alloying technique can open up a new direction to further explore different alloy systems (binary or ternary alloys) with even lower melting point. Abstract : Sn‐rich perovskite solar cells with large grains are fabricated from a Pb–Sn eutectic alloy in the liquid phase by using a chemical vapor deposition technique, resulting in a device power conversion efficiency of 14.04%, which is comparable with that of pure Pb devices and among the highest for Sn‐rich binary Sn/Pb metal perovskite solar cells.